Mechanism the land subsidence from multiple spatial scales and hydrogeological conditions – A case study in Beijing-Tianjin-Hebei, China. - Jiao Han; Huili Gong; Lin Guo; Xiaojuan Li; Lin Zhu; Beibei Chen; Qingquan Zhang; Le Wu; Jinyu Lei; Xueqi Zhu (Journal of Hydrology: Regional Studies, 2023)
Study region: Beijing-Tianjin-Hebei (BTH) region, China Study focus: BTH has long been suffering from severe and uneven land subsidence. Finding out the spatial evolution of land subsidence is helpful to collaborative prevention and control. We innovatively revealed the spatial distribution of land subsidence from the mountains to the coastal area along four hydrogeological profiles, and inferred the land subsidence mechanism on the overall scale, local plain scale and typical regional scale. Small Baseline Subsets Interferometric Synthetic Aperture Radar was employed to collect displacement information in the BTH region from January 2012 to January 2020. We obtained groundwater storage data from the Gravity Recovery and Climate Experiment. New hydrological insights for the region: On the overall scale, from 2012 to 2019, the Changping-TongZhou district of Beijing suffered the most serious land subsidence, with an annual subsidence rate of 159 mm and a cumulative subsidence as high as 928 mm. On the local plain scale, areas experiencing severe subsidence were generally located in the central plain. Fractures in the area obviously influenced the spatial distribution of subsidence. On the typical regional scale, a positive correlation was found between land subsidence and groundwater depletion. The relationship between precipitation and land subsidence in Hebei was the most convincing (R2 = 0.64). This study provides a scientific basis for regional coordination in land subsidence control. Data availability: Data can be provided by the corresponding authors upon request.